Amelioration of isoniazid and rifampicin-induced liver toxicity by Amaranthus graecizans subsp. silvestris in rat - Ishtiaq, Saiqa; Khan Afridi, Muhammad Shaharyar; Masood, Nawal (Bangladesh Journal of Pharmacology, 2017)
Amaranthus graecizans subsp. silvestris, a folk medicine for the treatment of inflammation, was used to evaluate its hepatoprotective potential against rifampicin and isoniazid-induced liver damage. Wistar albino rats were divided into four groups: Group I served as control (distilled water treated), Group II served as hepatotoxic group (isoniazid 50 mg/kg and rifampicin 100 mg/kg, treated), Group III served as positive control (silymarin 100 mg/kg, treated) while Group IV served as A. graecizans subsp. silvestris extract (400 mg/kg) treated group. The results suggest that the liver markers (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and total bilirubin) were significantly increased in the animals of Group II. The methanolic extract showed a significant decrease in the raised liver enzymes of Group IV and encountered the liver damage caused by isoniazid and rifampicin. Histopathological examination of liver also revealed the improved architecture in the extract-treated group. Thus, the methanolic extract has potential liver protective action due to its phytochemicals. Video Clip of Methodology: 8 min 24 sec: Full Screen Alternate